Identification of Drosophila cytoskeletal proteins by induction of abnormal cell shape in fission yeast. - Edwards, K.A.; Montague, R.A.; Shepard, S.; Edgar, B.A.; Erikson, R.L.; Kiehart, D.P. (Proceedings of the National Academy of Sciences of the United States of America, 1994)
To clone metazoan genes encoding regulators of cell shape, we have developed a functional assay for proteins that affect the morphology of a simple organism, the fission yeast Schizosaccharomyces pombe. A Drosophila melanogaster cDNA library was constructed in an inducible expression vector and transformed into S. pombe. When expression of the Drosophila sequences was induced, aberrant cell shapes were found in 0.2% of the transformed colonies. Four severe phenotypes representing defects in cytokinesis and/or cell shape maintenance were examined further. Each displayed drastic and specific reorganizations of the actin cytoskeleton. Three of the cDNAs responsible for these defects appear to encode cytoskeletal components: the actin binding proteins profilin and cofilin/actin depolymerizing factor and a membrane-cytoskeleton linker of the ezrin/merlin family. These results demonstrate that a yeast phenotypic screen efficiently identifies conserved genes from more complex organisms and sheds light on their potential in vivo functions.